Accounting for the ecological dimension in participatory research and development: lessons learned from Indonesia and Madagascar - Laumonier, Y.; Bourgeois, R.; Pfund, J.L. (2008)
The lack of understanding on how to integrate ecological issues into so-called socialecological natural resource management hampers sustainability in tropical forest landscape management. We build upon a comparison of three cases that show inverse gradients of knowledge and perceptions of the environment and human pressure on natural resources. We discuss why the ecological dimension currently lags behind in the management of tropical forest landscapes and to what extent participatory development can enhance the fit among ecological, socio-cultural, and economic systems. For each case study, socio-cultural and anthropological aspects of society and indigenous knowledge of the environment, the distribution of natural resources, classification, and management are documented in parallel with biophysical studies. Our results confirm that the ecological dimension remains weakly addressed and difficult to integrate into development actions when dealing with tropical forested landscape management in developing countries. We discuss three issues to understand why this is so: the disdain for traditional ecological knowledge and practices, the antagonism between economy and ecology, and the mismatch between traditional and modern governance systems. Participatory development shows potential to enhance the fit among ecological, socio-cultural, and economic systems through two dimensions: the generation and sharing of information to understand trends and the generation of new coordination practices that allow stakeholders to voice environmental concerns. In the absence of a “champion,” institutions, and financial resources, the expected outcomes remain on paper, even when changes are negotiated. Future research in natural resource management must emphasize better integration at the interface of ecology and governance. Finally, we identify three challenges: the design of operational tools to reconcile ecology with social and economic concerns, the creation of governance systems to institutionalize collaborative and integrated resource management, and the design of enabler organizations close to local communities